Rowing on a boat versus rowing on an ergo-meter: a biomechanical and electromyographycal preliminary study - Marcolin, G.; Lentola, A.; Paoli, A.; Petrone, N. (Procedia Engineering, 2015)
The present preliminary study aimed to report differences between rowing on a boat and rowing on ergo-meter considering not only kinetics and kinematics but also electromyography for a wider understanding of the motor control patterns. Right elbow and knee kinematics of a 23 years old elite rower was recorded by means of two electrical goniometers. Resultant handle force was calculated respectively from strain gauges applied on the right oar and with an uni-axial load cell fixed on the ergo-meter bar. Eight muscles were considered, referred to right arm, right leg and trunk. The athlete was asked to perform 2 minutes rowing on-water at 20 strokes per minute (spm) and 2 minutes at 32 spm. Then he performed the same protocol on the rower ergo-meter. Maximal voluntary contractions were recorded for EMG data normalization. Kinematics showed an increase in the elbow peak flexion (+20.3% at 20 spm and +16.6% at 32 spm) and a decrease in the knee peak flexion (-4.5% at 20 spm and -2.8% at 32 spm) rowing on the ergo-meter. Peak force recorded at the right hand was higher in the ergo-meter both at 20 spm (+43.5%) and at 32 spm (+29.8%). Muscle activity was higher in the ergo-meter considering biceps brachii, deltoideus medialis, trapezius trasversalis and vastus medialis. Cross-plots of elbow flexion versus muscle activity and versus hand force showed different coordinative patterns comparing the two experimental conditions. Results of this preliminary study indicated the ergo-meter as a valid training device considering the force at the hand. However, it showed different coordinative patterns with respect to rowing on the water in such a way that it should be carefully employed close to competitions.